Frequency of Malignancy in Clinically Benign Breast Lump - Sindhu, Shaista; Katiar, Ishrat Rahim; Khatoon, Shahida; Shah, Syed Amir; Dev, Kapil; Katiar, Saddam Hussain (Biological and Clinical Sciences Research Journal, 2025)
Breast lumps are among the most common presentations in surgical clinics, and while many are benign, a significant proportion may harbor malignancy. Clinical assessment alone may not reliably differentiate benign from malignant lesions, necessitating histopathological confirmation to guide appropriate management. Objective: To determine the frequency of malignancy in clinically benign breast lumps. Study design: Cross-sectional study. Place and duration: Department of General Surgery, Liaquat University of Medical and Health Sciences, Jamshoro, for 6 months, i.e., from September 2024 to February 2025. Methods: A total of 143 patients who fulfilled the selection criteria were included. At baseline, the demographic profile, clinical history, and physical examination of all patients were carried out, and findings were not noted down on a predesigned proforma by the researcher herself. Risk factors for malignancy were assessed in all patients. All patients were then subjected to core needle biopsy of the breast lump. Specimens were sent for histopathological evaluation, and findings were noted down and subjected to statistical analysis. Results: The median (IQR) age of the patients was 52 (16) years. The median (IQR) BMI was 25.4 (4.8) kg/m2. The median (IQR) duration of BBL was 4 (2) months. Among patients with BLL, malignancy was reportedly present in 28 (19.6%) patients. Conclusion: In patients with benign breast lesions, malignancy was reported in 28 (19.6%) patients.